El turismo de aventura: estudio de caso comunidad de Oyacachi, Cantón El Chaco, Provincia de Napo. - Aigaje Quinatoa, Fabián Mijaíl (2022)
This research called "Adventure tourism: case study community of Oyacachi, canton El Chaco, Napo province" has a qualitative approach using bibliographic and field method, same that were used to meet set objectives, being primary: to determine activities of adventure tourism at Kichwa Oyacachi community through collection of primary and secondary information, to boost local economy, through a case study. The research project was born from lack knowledge of the community about adventure tourism, causing waste of natural resources and focusing on livestock and agriculture, in addition, it is known that there is poor support from authorities at tourism sector. In response to the problem, three specific objectives have been set, the first one is to describe tourist demand, for this purpose survey technique was used, which was made up 19 closed questions. For its application, the non-probabilistic sampling method of convenience and criterion sampling was used in order to know preferences of the tourist profile in relation to adventure tourism. For second objective, was to identify tourist offer, a second survey was used, made up of 12 closed questions, using Likert scale to evaluate the opinion and attitude of the tourist service providers in Oyacachi. It is necessary to mention that for instrument validation, the opinion of teaching experts was requested and survey was applied to 20 people. The most relevant result indicates that both tourists and service providers determine that adventure sports will be well received, given that favorable geographic spaces for this type of tourism. The proposal of the present work responds to third objective proposing adventure tourism alternatives through the elaboration of technical manuals for climbing-rappel, hiking and recreational fishing with their respective guidelines. These manuals consist of following sections: location map elaborated through ArcGIS with GPS data, description of the area, regulations, technical manuals, basic equipment, permissions, restrictions, and cost. It is concluded that Oyacachi community has natural resources necessary to implement adventure tourism and is considered a safe place to carry out this project.